Ambient pressure photoelectron spectroscopy: Practical considerations and experimental frontiers. (2nd December 2016) - Trotochaud, Lena; Head, Ashley R; Karslıoğlu, Osman; Kyhl, Line; Bluhm, Hendrik
Abstract: Over the past several decades, ambient pressure x-ray photoelectron spectroscopy (APXPS) has emerged as a powerful technique for in situ and operando investigations of chemical reactions under relevant ambient atmospheres far from ultra-high vacuum conditions. This review focuses on exemplary cases of APXPS experiments, giving special consideration to experimental techniques, challenges, and limitations specific to distinct condensed matter interfaces. We discuss APXPS experiments on solid/vapor interfaces, including the special case of 2D films of graphene and hexagonal boron nitride on metal substrates with intercalated gas molecules, liquid/vapor interfaces, and liquid/solid interfaces, which are a relatively new class of interfaces being probed by APXPS. We also provide a critical evaluation of the persistent limitations and challenges of APXPS, as well as the current experimental frontiers.